Cross-level research on the impact of self-serving leadership on employee innovation behavior: The roles of workplace anxiety and team psychological safety - Liu, Liangcan; Wan, Zhitao; Wang, Li (Frontiers in Psychology, 2023)
Employee innovative behavior is significant in maintaining an organization’s sustainable development. This research explored the impact of team psychological safety and workplace anxiety in the association self-serving leadership with employee innovation behavior by synthesizing the social information processing theory, conservation of resources theory, and ego depletion theory. We conducted a hierarchical linear model analysis using three-wave paired data collected from 86 leaders and 392 employees. The research results show that self-serving leadership is negatively correlated with Employee innovation behavior. meanwhile, team psychological safety and workplace anxiety mediated this relationship;. In addition, team psychological safety alleviates the impact of workplace anxiety on employee innovation behavior and the indirect impact of self-serving leadership on employee innovation behavior via workplace anxiety. these findings have a number of theoretical and practical implications in the domains of self-serving leadership and employee innovation behavior.